Learner-Centered Assessment: Requirements and Challenges of Implementation in Foreign Language Environments (مجلة الواحات للبحوث والدراسات, 2023)
Abstract:Although, Learner-Centered Teaching Methods Received Much Attention By Educators, Less, However, Has Been Done With Learner-Centered Assessment. In Algerian Universities, Namely, Batna2 University, And At The Department Of English Language And Literature, Students Usually Go Through Tests To Be Assigned A Grade That Informs About Their Learning. Yet, These Proved To Be Limited And Ineffective. Thus, And On The Basis Of These Facts, The Present Paper Aims At Clarifying Basic Concepts Related To Learner-Centered Assessment, By Reviewing The Main Literature About The Topic And Its Main Dimensions And Limitations. The Article Aims Also At Removing Any Ambiguities And At Making Its Implementation In Our Teaching Contexts Possible.Keywords:, Learner-Centered Assessment., Learner-Centered Environments., Requirements., Strategies., Challenges.